Macroeconomic forecasting with mixed frequency data: Forecasting US output growth - Michael P. Clements; Ana Beatriz Galv\~AƒÂo; Massimiliano Marcellino (Queen Mary University of London, Department of Economics, 2007)
Many macroeconomic series such as US real output growth are sampled quarterly, although potentially useful predictors are often observed at a higher frequency. We look at whether a mixed data-frequency sampling (MIDAS) approach can improve forecasts of output growth. The MIDAS approach is compared to other ways of making use of monthly data to predict quarterly output growth. The MIDAS specification used in the comparison employs a novel way of including an autoregressive term. We find that the use of monthly data on the current quarter leads to significant improvement in forecasting current and next quarter output growth, and that MIDAS is an effective way of exploiting monthly data compared to alternative methods. We also exploit the best method to use the monthly vintages of the indicators for real-time forecasting.
Keywords: C51; C53; 330; Mixed data frequency; Coincident indicators; Real-time forecasting; US output growth; Wirtschaftsprognose; Gesamtwirtschaftliche Produktion; Statistische Methode; Autokorrelation; USA